2003
DOI: 10.6013/jbrewsocjapan1988.98.293
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Low-amylose Rice Cultivars for Sake Brewing

Abstract: To investigate the suitability of low-amylose rice cultivars for sake brewing, weanalyzed physicochemical properties, and carried out small scale sake brewing and a Koji making test,with normal rice cultivars serving as controls.Important findings in this study are:(1) low-amylose rice the cultivars had a superior water absorption;(2)Dynamic modulus(G')of steamed rice of low-amylose rice cultivars was lower than in controls;in low-amylose rice cultivars,water content of polished rice does not greatly affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…It is important to elucidate the factors influencing enzyme digestibility, in part to aid in the development of new cultivars, and in the evaluation of rice quality for sake production. Among the many factors that affect enzymatic digestion of the steamed rice grains, recent research has been directed toward starch itself, the largest component of rice grains (Wakai et al 1997;Mizuma et al 2003;Aramaki et al 2004). Wakai et al (1997) and Mizuma et al (2003) reported that the amylose content of rice grains correlated negatively with enzyme digestibility, while Aramaki et al (2004) reported a negative correlation between the content of amylopectin long chains (DP 35-41) and enzyme digestibility.…”
mentioning
confidence: 96%
“…It is important to elucidate the factors influencing enzyme digestibility, in part to aid in the development of new cultivars, and in the evaluation of rice quality for sake production. Among the many factors that affect enzymatic digestion of the steamed rice grains, recent research has been directed toward starch itself, the largest component of rice grains (Wakai et al 1997;Mizuma et al 2003;Aramaki et al 2004). Wakai et al (1997) and Mizuma et al (2003) reported that the amylose content of rice grains correlated negatively with enzyme digestibility, while Aramaki et al (2004) reported a negative correlation between the content of amylopectin long chains (DP 35-41) and enzyme digestibility.…”
mentioning
confidence: 96%
“…The lower the amylose content of rice suitable for sake brewing, the later was the retrogradation of steamed rice (Wakai et al, 1997), and the higher the water absorptivity, digestibility and solubility in the unrefi ned sake (Mizuma et al, 2003). Therefore, the rice with a lower amylose content leaves a smaller amount of sake lees, and has a higher effi ciency of material use (Takayama et al, 1991a(Takayama et al, , 1991b.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that the lower the amylose content, the higher the suitability for sake brewing (Yoshizawa et al, 1981;Takayama et al, 1991aTakayama et al, , 1991bWakai et al, 1997;Mizuma et al, 2003). Recently, pasting properties examined with a rapid viscoanalyzer (RVA) and gelatinization properties examined with a differential scanning calorimetry (DSC) are used to analyze the properties of starch related to the suitability for sake brewing.…”
mentioning
confidence: 99%
“…New types of sake that take advantage of the characteristics of specialty rices were developed (Furukawa et al , 2004(Furukawa et al , 2005Mizuma et al 2002Mizuma et al , 2003. The suitability of various rice cultivars including low-glutelin and low-amylose rices for sake brewing was examined.…”
mentioning
confidence: 99%